Strategy for Improving the Quality of Waqf Institutions Through Good Waqf Governance - Syamsuri Syamsuri; Setiawan bin Lahuri; Wahyudi Bakri; Anwar Fatoni; Hendri Setyo Wibowo (University of Darusssalam Gontor, 2021)
The sustainability of the benefits of waqf is possible because of the implementation of productive waqf can support various social and religious activities. Even so, good and innovative management is still needed in order to achieve professional waqf management, namely good waqf governance. This paper aims to examine the concept of good governance, the potential of waqf in Indonesia, and the institutional problems and solutions of waqf in Indonesia. This is a library research using a qualitative method and descriptive analytic study. Data were collected using the documentary method, which comes from books, journals, internet, and papers. The results of this study indicate that the donated land assets in Indonesia are 52.245,41 hectares spread over 385.898 locations. Most of the use of the waqf land is still in the form of direct waqf (consumptive), dominated by the construction of mosques by 44,26% and musholla (a prayer room) by 28,43%. Meanwhile, the potential for cash waqf in Indonesia reaches 3 trillion per year with an estimated number of generous Muslims of 10 million and an average monthly income of IDR 500.000 to IDR 10.000.000. Regarding problems in the development of waqf related to waqf management, including the management that is not optimal, even many are mismanaged which results in many waqf assets being neglected, some even missing. The solution lies in the existence of nadzir and a solid team work to maximize the expected results of waqf where waqf management requires good governance which can be used as a benchmark for whether performance in the organization is based on five principles, namely transparency, accountability, responsibility, independence and fairness or not.